2021
DOI: 10.1007/s12031-021-01866-y
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Roles of COMT and GAD1 Genes in Patients with Treatment-Resistant Schizophrenia: a Genetic Association Study of Schizophrenia Patients and Healthy Controls

Abstract: BackgroundThe projection from dopaminergic neurons to gamma-aminobutyric acid (GABA) interneurons in the prefrontal cortex is involved in the etiology of schizophrenia. The impact of interacting effects between dopamine signals and the expression of GABA on the clinical phenotypes of schizophrenia has not been studied. Since these interactions could be closely involved in prefrontal cortex functions, patients with speci c alleles of these relevant molecules (which lead to lower or vulnerable genetic functions)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…Notably, a recent genetic association study has reported that the percentage of treatment resistant patients with the Met allele of rs4680 on the COMT gene and C/C homozygote of rs3470934 on the glutamate decarboxylase 1 ( GAD1 ) gene was significantly higher than in treatment responders and healthy control subjects [ 79 ]. The authors speculated that the Met/CC allelic combination may predispose to TRS as a consequence of higher dopamine levels and lower γ-Aminobutyric acid (GABA) expression in the prefrontal cortex (PFC), thereby causing an excitation/inhibition imbalance that cannot be reverted by antipsychotics ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a recent genetic association study has reported that the percentage of treatment resistant patients with the Met allele of rs4680 on the COMT gene and C/C homozygote of rs3470934 on the glutamate decarboxylase 1 ( GAD1 ) gene was significantly higher than in treatment responders and healthy control subjects [ 79 ]. The authors speculated that the Met/CC allelic combination may predispose to TRS as a consequence of higher dopamine levels and lower γ-Aminobutyric acid (GABA) expression in the prefrontal cortex (PFC), thereby causing an excitation/inhibition imbalance that cannot be reverted by antipsychotics ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Kogure and colleagues [ 25 ] reported that COMT rs4680/GAD1 rs3749034 met(+)/T(𢄡) carriers were more likely to be found in the TRS group.…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the underlying biology of TRS and optimize its treatment, there is increasing interest in the genetic factors associated with TRS and clozapine treatment. For example, a recent genetic association study found that an interaction between the dopaminergic and γ-aminobutyric acid ( GABA ) signal intensities could differentiate patients with and without TRS [ 25 ]. Another recent study reported that the Glutamate Decarboxylase 1 ( GAD1 ) gene and the GABA Type B Receptor 2 ( GABBR2 ) gene were associated with TRS [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the evidence confirmed that the interaction between dopaminergic signaling and GABAergic gene expression affects the clinical phenotype of schizophrenia which can help identify TRS patients. Specifically, the percentage of subjects with Met allele of rs4680 on the COMT gene and C/C homozygote of rs3470934 on the GAD1 gene was significantly higher in the TRS group than non-TRS group and HC group ( Kogure et al, 2021 ).…”
Section: Peripheral Biomarkersmentioning
confidence: 91%
“…While altered dopaminergic function is the main feature of schizophrenia, patients with TRS might have distinct patterns in dopaminergic abnormality ( Kogure et al, 2021 ). Specifically, as compared with patients with treatment-responsive schizophrenia, decreased dopamine synthetic capacity in striatum, decreased dopaminergic synaptic density and dopamine transporter protein expression in caudate nucleus have been reported in TRS patients ( Demjaha et al, 2012 ; Sagud et al, 2018 ).…”
Section: Peripheral Biomarkersmentioning
confidence: 99%